Analysis of soil bacteria susceptibility to manufactured nanoparticles via data visualization - Liu, Rong; Ge, Yuan; Holden, Patricia A.; Cohen, Yoram (Beilstein Journal of Nanotechnology, 2015)
The impact of ZnO and TiO2 manufactured nanoparticles (MNPs) on soil bacterial communities for different exposure periods and MNP doses was explored via data visualization techniques. Interrelationships between MNP treatments and responses of bacterial taxa were illustrated by bipartite graphs, allowing fast identification of important soil bacterial taxa that are susceptible to MNPs. Contribution biplots with subcompositional coherence property were generated via log-ratio analysis (LRA), which jointly display the treatment distribution and the variance (contribution) of bacterial taxa. The LRA contribution biplots and nonmetric multi-dimensional scaling (NMDS) of the dataset, along with hierarchical clustering, demonstrated that high doses of ZnO and TiO2 MNPs caused significant compositional changes in soil bacterial communities. The suitability of family level for MNP taxonomic impact assessment was demonstrated by both the LRA biplots and simplified NMDSs with quantification provided by the distance correlation between MNP impacts summarized at different taxonomic levels. The present study demonstrates that visual exploration could potentially assist in knowledge discovery and interpretation of data on soil bacterial communities exposed to MNPs and thus evaluate the potential for environmental impacts.
Keywords: environmental impact; manufactured nanoparticles; nanoinformatics; soil bacteria; visualization

Textbook of Nanoscience and Nanotechnology - Murty, B. S.; Shankar, P.; Raj, B.; Rath, B. B.; Murday, J. (Springer, 2013)

Fundamentals and Applications of Nanomaterials - Guo, Z.; Tan, L. (Artech House Publishers, 2009)

Inventory Finds Increase in Consumer Products Containing Nanoscale Materials - The Wilson Center

(untitled) - Nel, A.; Xia, T.; Mädler, L.; Li, N. (Science, 2006)

(untitled) - Xia, T.; Malasarn, D.; Lin, S.; Ji, Z.; Zhang, H.; Miller, R. J.; Keller, A. A.; Nisbet, R. M.; Harthorn, B. H.; Godwin, H. A.; Lenihan, H. S.; Liu, R.; et al. (Small, 2013)

(untitled) - Handy, R. D.; Shaw, B. J. (Health Risk Soc., 2007)

(untitled) - Helland, A.; Scheringer, M.; Siegrist, M.; Kastenholz, H. G.; Wiek, A.; Scholz, R. W. (Environ. Sci. Technol., 2007)

(untitled) - Hristozov, D. R.; Gottardo, S.; Critto, A.; Marcomini, A. (Nanotoxicology, 2012)

(untitled) - Grieger, K. D.; Linkov, I.; Hansen, S. F.; Baun, A. (Nanotoxicology, 2012)

(untitled) - Colvin, V. L. (Nat. Biotechnol., 2003)

(untitled) - Gerber, C.; Lang, H. P. (Nat. Nanotechnol., 2006)

(untitled) - Scown, T. M.; van Aerle, R.; Tyler, C. R. (Crit. Rev. Toxicol., 2010)

(untitled) - Cohen, Y.; Rallo, R.; Liu, R.; Liu, H. H. (Acc. Chem. Res., 2013)

(untitled) - Liu, H. H.; Cohen, Y. (Environ. Sci. Technol., 2014)

(untitled) - Gottschalk, F.; Sonderer, T.; Scholz, R. W.; Nowack, B. (Environ. Sci. Technol., 2009)

(untitled) - Klaine, S. J.; Alvarez, P. J. J.; Batley, G. E.; Fernandes, T. F.; Handy, R. D.; Lyon, D. Y.; Mahendra, S.; McLaughlin, M. J.; Lead, J. R. (Environ. Toxicol. Chem., 2008)

(untitled) - Tiede, K.; Hassellöv, M.; Breitbarth, E.; Chaudhry, Q.; Boxall, A. B. A. (J. Chromatogr. A, 2009)

(untitled) - Ge, Y.; Schimel, J. P.; Holdena, P. A. (Appl. Environ. Microbiol., 2012)

(untitled) - Ge, Y.; Schimel, J. P.; Holden, P. A. (Environ. Sci. Technol., 2011)

(untitled) - Ju-Nam, Y.; Lead, J. R. (Sci. Total Environ., 2008)

(untitled) - Navarro, E.; Baun, A.; Behra, R.; Hartmann, N. B.; Filser, J.; Miao, A.-J.; Quigg, A.; Santschi, P. H.; Sigg, L. (Ecotoxicology, 2008)

(untitled) - Baun, A.; Hartmann, N. B.; Grieger, K.; Kusk, K. O. (Ecotoxicology, 2008)

(untitled) - Asharani, P. V.; Lianwu, Y.; Gong, Z.; Valiyaveettil, S. (Nanotoxicology, 2011)

(untitled) - Gagné, F.; Auclair, J.; Turcotte, P.; Fournier, M.; Gagnon, C.; Sauvé, S.; Blaise, C. (Aquat. Toxicol., 2008)

(untitled) - Du, J.; Wang, S.; You, H.; Zhao, X. (Environ. Toxicol. Pharmacol., 2013)

(untitled) - Tong, Z.; Bischoff, M.; Nies, L.; Applegate, B.; Turco, R. F. (Environ. Sci. Technol., 2007)

(untitled) - Madsen, E. L. (Nat. Rev. Microbiol., 2005)

(untitled) - Falkowski, P. G.; Fenchel, T.; Delong, E. F. (Science, 2008)

(untitled) - Xue, K.; Wu, L.; Deng, Y.; He, Z.; Van Nostrand, J.; Robertson, P. G.; Schmidt, T. M.; Zhou, J. (Appl. Environ. Microbiol., 2013)

(untitled) - He, S.; Feng, Y.; Ren, H.; Zhang, Y.; Gu, N.; Lin, X. (J. Soils Sediments, 2011)

(untitled) - Nogueira, V.; Lopes, I.; Rocha-Santos, T.; Santos, A. L.; Rasteiro, G. M.; Antunes, F.; Gonçalves, F.; Soares, A. M. V. M.; Cunha, A.; Almeida, A.; Gomesa, N. N. C. M.; Pereirae, R. (Sci. Total Environ., 2012)

Multivariate Analysis of Ecological Data - Greenacre, M.; Primicerio, R. (Fundación BBVA, 2013)

(untitled) - Dormann, C. F.; Strauss, R. (Methods Ecol. Evol., 2014)

(untitled) - Dormann, C. F.; Fründ, J.; Blüthgen, N.; Gruber, B. (Open Ecol. J., 2009)

(untitled) - Dormann, C. F.; Gruber, B.; Fründ, J. (R News, 2008)

Compositional Data Analysis - Greenacre, M. (Compositional Data and Correspondence Analysis, 2011)

(untitled) - Greenacre, M.; Lewi, P. (J. Classif., 2009)

Data Mining: Concepts and Techniques - Han, J.; Kamber, M.; Pei, J. (Morgan Kaufmann, 2011)

Data Mining: Introductory and Advanced Topics - Dunham, M. H. (Prentice Hall, 2002)

Multidimensional Scaling - Cox, T. F.; Cox, M. A. A. (CRC Press, 2010)

(untitled) - Székely, G. J.; Rizzo, M. L.; Bakirov, N. K. (Ann. Stat., 2007)

(untitled) - Miller, R. J.; Lenihan, H. S.; Muller, E. B.; Tseng, N.; Hanna, S. K.; Keller, A. A. (Environ. Sci. Technol., 2010)

Matrix Computations - Golub, G. H.; Van Loan, C. F. (John Hopkins University Press, 2012)

(untitled) - Goslee, S. C.; Urban, D. L. (J. Stat. Software, 2007)

Modern Applied Statistics with S - Venables, W. N.; Ripley, B. D. (Springer, 2002)

All of Statistics: A Concise Course in Statistical Inference - Wasserman, L. (Springer, 2004)

(untitled) - Sun, L.; Ji, S.; Ye, J. (IEEE Trans. Pattern Anal. Mach. Intell., 2011)

(untitled) - Peter, J.; Young, W.; Haukka, K. E. (New Phytol., 1996)

(untitled) - Wilson, M. K.; Lowe, W. H.; Nislow, K. H. (J. For., 2014)